La Passione E La Croce Di Cristo Nel "Liber" Di Angela Da Foligno: Considerazioni preliminari - Vedova, Massimo (Miscellanea francescana, 2024)
Mystical texts, by their very nature, are open to multiple interpretations and have the ability to probe the mysteries of the Christian faith from a different viewpoint rather than the official theology of the historical context in which they are inserted. In particular, this can be said of the Liber by Angela of Foligno (1248-1309) in which the mystery of the cross and the passion of the Lord Jesus is explored in a singular and personal way through an experience of notable spiritual value. The richness of the text goes beyond the space of a simple article for which the work is limited to suggesting paths of reading and study.